Review Villegas Delgado, César .: Biosafety, Bioterrorism, and Human Rights in Contemporary International Law, Editorial Tirant lo Blanch, Valencia, 2020, 244 pages. ISBN 978-84-1336-470-4 - Bentaouet, Mohamed Saad (IUS ET SCIENTIA, 2021)
Review of the work: Villegas Delgado, César .: Biosafety, Bioterrorism, and Human Rights in Contemporary International Law, Editorial Tirant lo Blanch, Valencia, 2020, 244 pages. ISBN 978-84-1336-470-4